Pengaruh good corporate governance terhadap profitabilitas dengan pengungkapan tanggung jawab sosial perusahan sebagai variabel intervening pada perusahan LQ 45 yang terdaftar di Bursa Efek Indonesia - Havit Kurniawan Purnama; Sri Trisnaningsih (Proceeding of National Conference on Accounting & Finance, 2020)
The research aims to determine the effect of GCG (institutional ownership, managerial ownership, board of commissioners, audit committee) and profitability on CSR disclosure in LQ45 companies in 2016 - 2018. Research data were obtained from the IDX (Indonesia Stock Exchange). This type of research is a quantitative research method. The population in the study consisted of LQ 45 companies listed on the Indonesia Stock Exchange in 2016 - 2018 were 56 companies while the samples that met the criteria were 37 companies. The author uses path analysis, multiple regression analysis, as data analysis.